Fertility response following ablation-induced follicular wave emergence and ovulation induction in anestrous buffaloes - HONPARKHE, MRIGANK; GANDOTRA, VINOD KUMAR; BRAR, PARKASH SINGH; MALIK, ASLOOB AHMED; DADARWAL, DINESH; SINGH, JASWANT (The Indian Journal of Animal Sciences, 2022)
The fertility response following induction of follicular wave emergence by follicle ablation combined withprogesterone based ovulation synchronization in postpartum anestrous buffaloes was assessed. Postpartum anestrousbuffaloes (n=24) with absence of overt estrus signs categorized as treatment group (Group 1; n=15) and controlgroup (Group 2; n=9). Group 1 was subjected to transvaginal ultrasound-guided follicle ablation on a random dayof the estrous cycle (Day=0) and insertion of CIDR. Seven days later, CIDR was removed and prostaglandin F2Î±analogue was given intramuscularly. GnRH analogue was injected on day 9.5 and fixed-time AI was done 12 h and24 h later. Ultrasonography was performed to follow ovarian structures on different occasions and on day 38 postovulationfor detecting pregnancy. Group 2 did not receive any treatment however, estrus detection in this groupwas done daily by bull parading and visual monitoring followed by AI if found in standing estrus. In treatmentgroup, the follicular wave emergence occurred by 24 h following ablation in 60% buffaloes and in 40% remaininganimals by 48 h. The estrus exhibition was 100 % in group 1 versus 22.2 % in group 2. Mean interval from CIDRremoval to ovulation was 81.2Â±3.08 h and from wave emergence to ovulation was 9.92Â±0.18 days. The first servicepregnancy rate in treatment group was higher than control (66.67% vs 22.2%). The induction of follicular waveemergence through ultrasound guided follicle ablation and progesterone based ovulation synchronization can beused to improve pregnancy rates in anestrous buffaloes.